MASALAH-MASALAH YANG DIALAMI SISWA SMP N XIII KOTO KAMPAR T.P 2015/2016 - Saripah '; Elni Yakub; Zulfan Saam (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: The objectives of this research are 1) to analyze personal problems of male and female students, 2) to analyze emotional problems of male and female students, 3) to analyze learning problems, 4) to analyze family problem of male and female students, 5) to analyze social problems of male and female students, 6) to analyze the problems that experienced by male and female students in general, 7) to analyze the category of the students’ problems in general. The instrument of collecting data is a questioner. The using of this questioner is in order to obtain data regarding the preference of students’ problems based on personal, emotional, learning, family and social aspects. The subject of this research is all of the students of Junior High School Number 1 Kampar Koto Kampar class VII, VIII and IX that consist of 0f 210 students. Sampling is determined by applying total sampling, that all of the population members are the samples. The result shows that 53 male students (58%) and 52 female students (44%) experienced personal problems especially for self confident, they are included in the middle category, 2) 43 male students (58%) and 63 female students (53%) female students experienced emotional problem especially for sadness, they are included in the middle category, 3) 49 (53%) male students experienced learning problem especially about learning motivation and 63 (53%) female students experienced learning problem especially about learning achievement both of them included in middle category, 4) 66 (72%) male students and 81 (69)% female students experienced family problem especially about the relationship with their parents, they are included in the few category, 5) 66 (72%) male students experienced social problem related to students and teachers relationship and 78 (70%) female students experienced the same problem but related to relationship with friends at the same age, both of them included in few category, 6) The problems of personal, emotional, learning, family and social aspects experienced by male and female students is the family aspect especially in learning motivation, it is included in the middle category. 7) the problem experienced by male and female students that included in the many category is the emotional problem (15%), especially about the sadness.Keywords: Students’ problems